2000
DOI: 10.1016/s0735-1097(00)00779-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary cerebral resuscitation using emergency cardiopulmonary bypass, coronary reperfusion therapy and mild hypothermia in patients with cardiac arrest outside the hospital

Abstract: The alternative CPCR demonstrated an improvement in the incidence of good recovery. Based upon these findings, randomized studies of this hypothermia are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(107 citation statements)
references
References 32 publications
4
99
0
4
Order By: Relevance
“…[13][14][15][16] On the other hand, Nagao et al also used the Utstein guidelines and showed that the proportion of VF or pulseless VT as the first cardiac rhythm was 38% with a mean call-to-scene interval of approximately 5.5 min, 26 and the cause of VF was acute coronary syndrome in 78%, which included the initial angiogram of the acute coronary syndrome related artery that had Thrombolysis in Myocardial Infarction flow grade 0-2 in 77%. 27 The Utstein guidelines for cardiac arrest are intended to provide a structure for evaluating an EMS system and the usefulness of the Utstein style has been confirmed by the many communities that have identified weakness in the "Chain of Survival" of their emergency cardiovascular care. 5,16 The studies conducted according to the Utstein style have indicated that there are several characteristics of the EMS system in Japan that account for the low proportion of VF or pulseless VT as the first cardiac rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] On the other hand, Nagao et al also used the Utstein guidelines and showed that the proportion of VF or pulseless VT as the first cardiac rhythm was 38% with a mean call-to-scene interval of approximately 5.5 min, 26 and the cause of VF was acute coronary syndrome in 78%, which included the initial angiogram of the acute coronary syndrome related artery that had Thrombolysis in Myocardial Infarction flow grade 0-2 in 77%. 27 The Utstein guidelines for cardiac arrest are intended to provide a structure for evaluating an EMS system and the usefulness of the Utstein style has been confirmed by the many communities that have identified weakness in the "Chain of Survival" of their emergency cardiovascular care. 5,16 The studies conducted according to the Utstein style have indicated that there are several characteristics of the EMS system in Japan that account for the low proportion of VF or pulseless VT as the first cardiac rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…These studies led to the preliminary clinical research on mild hypothermia. Preliminary clinical studies have shown that patients treated with mild hypothermia after cardiac arrest have improved neurologic outcome, without noticeable side effects, as compared to the outcome in historical controls [81][82][83][84]. Recently, Young et al [85] hypothesized that TH can be used to improve survival and reduce neurologic injury in adult patients with HF postarrest.…”
Section: Therapeutic Hypothermiamentioning
confidence: 99%
“…Es ist anerkannt, das Patienten nach einem Kreislaufstillstand mit ST-Hebungs-Infarktzeichen (STEMI) schnellstmöglich eine Koronarangiographie und eine PCI erhalten sollen. Da jedoch sowohl Thoraxschmerz als auch ST-Veränderungen bei den Patienten nach Kreislaufstillstand nur eingeschränkt korrekt einen akuten koronaren Verschluss voraussagen [660], soll bei allen Patienten nach Kreislaufstillstand, bei denen eine KHK angenommen werden kann, eine PCI in Erwägung gezogen werden [630,634,660,661,662,663,664,665,666]. Mehrere Studien weisen darauf hin, dass bei einem Patienten mit einem Kreislaufstillstand, der aufgrund eines ACS aufgetreten ist, die Kombination von Hypothermie und PCI machbar sowie sicher ist [630,634,639,666,667].…”
Section: Herz-kreislauf-systemunclassified